Rheumatoid arthritis-associated uveitis treated with adalimumab - Kalaczyńska, Elżbieta; Bilińska, Ewa; Owidzka, Marta; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
Uveitis is an inflammatory ocular disorder of various aetiology affecting the middle vascular layer of the eye. The condition mainly affects relatively young patients and if untreated, it can lead to significant complications, including blindness. Hence, it is of a critical importance to prevent inflammation and vision loss in eyes with uveitis. Here, we report a case of a 36-year-old male with a history of rheumatoid arthritis, who was first diagnosed with anterior uveitis, and subsequently presented with macular oedema and epiretinal membranes. However, conventional treatment with a steroid was not sufficient to control the inflammation and was associated with elevated intraocular pressure as a side effect. Eventually, the patient was treated with adalimumab, which effectively prevented disease progression and resolved his rheumatoid symptoms.